An economic decision model for determining the appropriate level of business process standardization - Patrick Afflerbach; Manuel Bolsinger; Maximilian Röglinger (Business Research, 2016)
Business process management (BPM) is an acknowledged source of corporate performance. A well-established element of the BPM toolbox by which organizations intend to tune the performance of their processes is business process standardization (BPS). So far, research on BPS has predominantly taken a descriptive perspective, analyzing how BPS affects different dimensions of process performance (e.g., cost, quality, time, flexibility). Only very few studies capitalize on the mature body of descriptive BPS knowledge to assist in determining an appropriate BPS level for an organization's processes. Moreover, these studies do not resolve the BPS trade-off, i.e., the partly conflicting effects of BPS on process performance. To address this research problem, we propose a decision model that provides guidance on how to determine an economically appropriate BPS level for a business process. We thereby adopt the design science research (DSR) paradigm and draw from the body of knowledge on BPS as well as value-based management. We evaluated the decision model by discussing its design specification against theory-backed design objectives. We also validated the model's applicability and usefulness in a real-world case where we applied the decision model and a prototypical implementation to the coverage switching processes of an insurance broker pool company. Finally, we challenged the decision model against the accepted evaluation criteria from the DSR literature.
Keywords: 650; Business process management; Business process standardization; Decision model; Process performance management; Value-based management